A Study on Women Empowerment in South-Asian Countries: A Contemporary Analysis - Nelasco, Shobana (Mediterranean Journal of Social Sciences, 2012)
Women are marginalized in the human society from the day of its origin in all parts of the world. Like anyother region of the world, south Asia is not a region, with this major problem. This paper is an attempt tomake a comparative analysis on Women empowerment in seven South Asian countries. Since internationalcomparison provides us a better comparison of status, ranking is compared mainly. This comparison can bedone effectively by comparing few indices like Gender Related Development index, Gender empowermentmeasure, Gender inequality in Education, Gender Inequality in Economic activity, Political EmpowermentMeasure etc. This paper is a small piece of a major research done over this area. This paper has comparedonly the comparative women empowerment indicators like Gender Related Development index and Genderempowerment measure for a point of time and found that women are not in equal status throught thisSouth Asian Region. Again Gender Development index ranking and Human Development Ranking aloneare compared over a period of time ie. from 1994 to 2011. The overall analysis has brought a conclusionthat South Asia is a region that need special attention from the world and international agencies for itsgender empowerment and human development as they are ranked beyond 134th Rank in HumanDevelopment Index and are placed beyond 98th rank in case of Gender Development Index except in caseof Sri lanka and Maldives where there are continuous crisis.